1996
DOI: 10.1046/j.1537-2995.1996.36696269516.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (HCV) genotype analysis in apparently healthy anti‐ HCV‐positive Parisian blood donors

Abstract: Among the sampled population, an HCV prevalence rate of 0.26 percent was found, with the five most common European genotypes causing the infections. Four new subtypes were discovered. Correlation between genotype and risk factors was not apparent, but links with age, sex, and ethnic origin emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
4
3
0
1
Order By: Relevance
“…The five main HCV genotypes were found among French blood donors as already reported [12]. We confirm that 1b is the most prevalent genotype among European donors [12]and patients [13], followed by 3a.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The five main HCV genotypes were found among French blood donors as already reported [12]. We confirm that 1b is the most prevalent genotype among European donors [12]and patients [13], followed by 3a.…”
Section: Discussionsupporting
confidence: 88%
“…We confirm that 1b is the most prevalent genotype among European donors [12]and patients [13], followed by 3a. We also found that IVDU and a history of blood transfusion are the main routes of HCV transmission, as observed in French studies [14, 15]and in other European countries [16, 17].…”
Section: Discussionsupporting
confidence: 75%
“…We could determine the serotype of 55 (80.9%) of the 68 samples, which is comparable with some other studies reporting 81.2% and 83%, respectively [16,17]. Serotypes 1 and 3 were the most prevalent serotypes among the Belgian population, confirming another Belgian study [18] which enrolled fewer patients from Flanders, as well as other studies among the European population [19][20][21][22][23]. Although these studies established the genotype instead of the serotype, the results can be compared since results obtained through genotyping and serotyping carried out using SA1-6 show a good correlation [16,17,24].…”
Section: Discussionsupporting
confidence: 88%
“…Numerous genotype distribution studies dating back to 1995 showed genotype 1 to be the most predominant (41,56,57,(78)(79)(80)(81)(82)(83)(84)(85). In the largest and best sample of HCV genotypes, 1769 samples were collected from 26 referral centres; 57% of the sample was genotype 1, 9.3% genotype 2, 20.8% genotype 3, 8.9% genotype 4, 2.7% genotype 5, 0.2% genotype 6 and 0.9% mixed genotypes (57).…”
Section: Genotype Distributionmentioning
confidence: 99%